Nursing Students’ Experiences of Palliative Care for Dying Patient - Hidayat, Ibnu Syarifudin; Damiati, Nia; Al Ayubi, Moch Thoriq Assegaf (Jurnal Keperawatan Soedirman, 2024)
A nurse requires to acquire the proper ability to care for dying patients. In nursing education, palliative care is a complex action that tends to be challenging for nursing students. This is because there is an interaction among learning professionalism, emotional empathy, and other grieving feelings related to the palliative conditions of the patient. Palliative care interventions provide various challenges and learning for nursing students according to socio-cultural and demographic characteristics. This study aimed to determine nursing students’ experiences of caring for dying patients. This research was qualitative research with a phenomenological design. The data was obtained through in-depth interviews. Based on data saturation, 12 informants had experiences of caring for dying patients within a previous year, obtained through a purposive sampling method. The audio recordings were collected and analyzed using the Collaizi technique. This study identified four themes: 1) feelings of caring for dying patients; 2) caring for dying patients; 3) self-influence in caring for dying patients; and 4) barriers to caring for dying patients. Feelings of fear, tension, confusion, and anxiety emerged when first time caring for a dying patient. The results of this study are expected as a reference for further research related caring for dying patients.